2000
DOI: 10.1152/ajpgi.2000.278.3.g416
|View full text |Cite
|
Sign up to set email alerts
|

Minor involvement of nitric oxide during chronic endotoxemia in anesthetized pigs

Abstract: Pastor, Catherine M., Antoine Hadengue, and Andreas K. Nussler. Minor involvement of nitric oxide during chronic endotoxemia in anesthetized pigs. Am. J. Physiol. Gastrointest. Liver Physiol. 278: G416-G424, 2000.-To study the modifications of hepatic blood flow and hepatic function over time during endotoxemia, 10 pigs received a continuous intravenous infusion of endotoxin (Endo, 160 ng · kg Ϫ1 ·h Ϫ1 ) over 18 h and 7 control (Ctrl) animals received a saline infusion. The involvement of nitric oxide (NO) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2003
2003
2005
2005

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…In fact, measuring the blood concentrations of the stable NO metabolites, namely NO 2 -and NO 3 -, may not be appropriate to estimate NO production in larger animals, in particular in pigs. Pastor et al [22] found no correlation between the NO production and the changes of plasma NO 2 /NO 3 levels either. This discrepancy may be due to marked changes in the total volume of distribution resulting from interstitial edema and flux into the third space, such as ascites [23].…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…In fact, measuring the blood concentrations of the stable NO metabolites, namely NO 2 -and NO 3 -, may not be appropriate to estimate NO production in larger animals, in particular in pigs. Pastor et al [22] found no correlation between the NO production and the changes of plasma NO 2 /NO 3 levels either. This discrepancy may be due to marked changes in the total volume of distribution resulting from interstitial edema and flux into the third space, such as ascites [23].…”
Section: Discussionmentioning
confidence: 94%
“…# designates significant differences versus baseline (P<0.05), § designates significant differences 1400W+NAD versus CON group stored blood pressure to baseline levels without affecting the cardiac output or regional hemodynamics and attenuated the detrimental consequences of endotoxin on intestinal and hepatic energy balance. In our model, the timing of treatment intervention was initiated 12 h after onset of LPS infusion to establish hyperdynamic circulation with concomitant signs of metabolic alterations, thereby closely mimicking the clinical situation, and allowing sufficient time for upregulation of iNOS expression [22]. It is still difficult to estimate the time and the quantity of NO production in larger animals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Total RNA was extracted from cultured hepatocytes as recently described [25]. Reverse transcription of total RNA to cDNA was carried out following a standard procedure and cDNA was amplified to detect HO-1 mRNA using specific primers based on the human HO-1 sequence: antisense 5 0 -TGC GGT GCA GCT CTT CTG-3 0 , sense 5-0 GCA ACC CGA CAG CAT GC-3 0 , amplifying a 244 bp product at cycles 35 [26].…”
Section: Isolation Of Rna and Rt-pcrmentioning
confidence: 99%
“…In experimental septic shock, an impaired response to vasoconstrictors is also observed in various regional circulations. In anesthetized pigs infused with endotoxin, we previously showed that the renal circulation was hyporesponsive to norepinephrine (Pastor, 1999), whereas the response of the hepatic circulation was not modified (Mastrangelo and Pastor, 1999;Pastor et al, 2000).…”
Section: Introductionmentioning
confidence: 98%